An Operational Financial Management Model and its Effect on the Profitability of the Transport Sector. Case of Company Bonanza S.A. - Ugando-Peñate, Mikel (2023)
This research focused the objective of optimizing financial processes and improving decision-making to have a positive effect on the profitability of the business, based on the proposal of an operational financial management model for the company Bonanza S.A. from the city of Santo Domingo. The methodology used focuses on a mixed approach, with a non-experimental cross-sectional design. The types of explanatory, comparative, descriptive and exploratory research have been used in order to meet the proposed objectives. Likewise, a logical order of financial techniques and tools was taken into account for the model proposal. From the analysis carried out based on the data collected, it is inferred that returns of cash equivalents due to non-compliance with contracts produced a loss in the year after the pandemic. The projections showed that the company has excess levels of external financing, although its debt levels are moderate in the current period analyzed. It is suggested to systematically monitor the applied techniques and a consequent analysis of the benefits in the management of contracts with public and private entities under terms that benefit the progress of the company.